Separation and identification of neutral oligosaccharides with prebiotic activities from apple pectin. (December 2021) - Liu, Huipeng; Wei, Xiaoyu; Zu, Shuyu; Lin, Xihuang; Zhang, Jinchuang; Shi, Aimin; Wang, Qiang; He, Ning
Abstract: Plant-derived neutral oligosaccharides and pectic-oligosaccharides (POS) have been suggested as prebiotics based on their degree of polymerization (DP) and structural complexity. In the present study, neutral oligosaccharides without galacturonic acid were produced from commercial apple pectin using an optimized concentration of pectinase and degradation time. The crude oligosaccharide solution was refined by membrane separation using a DEAE-Sepharose CL-6B column, a graphite carbon column and an Xbridge C18 column, which resulted in the neutral oligosaccharides with DP 3–13. The monosaccharide composition of oligosaccharides primarily included glucose, arabinose, galactose and xylose without galacturonic acid. The structure of the oligosaccharides was analyzed using mass spectrometry with an electrospray ionization source by UPLC on an HILIC column and 1 H NMR. The MS/MS spectra in positive ion mode and 1 H NMR showed a main oligosaccharide structure corresponding to the connection of arabinogalactan with Galβ1→4Galβ1→4Galβ1→4Galβ1→α3Ara f . The growth of the selected Lactobacillus . strains was improved by adding refined neutral oligosaccharides with DP = 3–13 compared with commercial inulin, and growth of Escherichia coli had not basically grown. Therefore, neutral oligosaccharides (DP = 3–13) can be considered effective prebiotics for potential application in functional food. Graphical abstract: Image 1 Highlights: A separation process was constructed for neutral pectin oligosaccharides (nPOS) preparation. Monosaccharide composition of nPOS contained no GalA and Rha. Main structure of nPOS was Galβ1. → 4Galβ1→4Galβ1→4Galβ1→α3Ara f Selected Lactobacillus. strains grew better by adding nPOS (DP 3–13) than inulin.